Practical quantum metrology in noisy environments - Nichols, Rosanna; Bromley, Thomas R.; Correa, Luis A.; Adesso, Gerardo (American Physical Society, 2016)
The problem of estimating an unknown phase ϕ using two-level probes in the presence of unital phase-covariant noise and using finite resources is investigated. We introduce a simple model in which the phase-imprinting operation on the probes is realized by a unitary transformation with a randomly sampled generator. We determine the optimal phase sensitivity in a sequential estimation protocol and derive a general (tight-fitting) lower bound. The sensitivity grows quadratically with the number of applications N of the phase-imprinting operation, then attains a maximum at some Nopt, and eventually decays to zero. We provide an estimate of Nopt in terms of accessible geometric properties of the noise and illustrate its usefulness as a guideline for optimizing the estimation protocol. The use of passive ancillas and of entangled probes in parallel to improve the phase sensitivity is also considered .We find that multiprobe entanglement may offer no practical advantage over single-probe coherence if the interrogation at the output is restricted to measuring local observables.